Crossing borders
1 online resource (xii, 295 pages)
Keywords: A set of essays intended to recognize the scholarship of Professor Cynthia Neville, the papers gathered here explore borders and boundaries in medieval and early modern Britain. Over her career, Cynthia has excavated the history of border law and social life on the frontier between England and Scotland and has written extensively of the relationships between natives and newcomers in Scotland’s Middle Ages. Her work repeatedly invokes jurisdiction as both a legal and territorial expression of power. The essays in this volume return to themes and topics touched upon in her corpus of work, all in one way or another examining borders and boundaries as either (or both) spatial and legal constructs that grow from and shape social interaction. Contributors are Douglas Biggs, Amy Blakeway, Steve Boardman, Sara M. Butler, Anne DeWindt, Kenneth F. Duggan, Elizabeth Ewan, Chelsea D.M. Hartlen, K.J. Kesselring, Tom Lambert, Shannon McSheffrey, and Cathryn R. Spence.